Estilos de vida saludables más comunes en los pacientes pertenecientes al Club de Diabéticos del Hospital General Isidro Ayora, periodo julio - diciembre 2016. - Ordóñez Campoverde, Diego Geovanny (2017)
Mellitus Diabetes is a chronic and severe disease, which has an impact on the health of diabetic patients, in addition to the enormous costs it generates; Health lifestyles like: hypocaloric feeding, physical exercise, help to prevent complications such as retinopathy, nephropathy, among others. The present research has as objective to determine the lifestyles of the patients of the diabetic club of the Hospital General Isidro Ayora and if these are healthy or not. The type of study is descriptive. In the study participated 51 people: 13 men and 38 women. Among the habits, it was found that 50.98% consume 3 to 5 meals a day, the most consumed foods are fruits and vegetables and carbohydrates with 39.22% and 19.61% respectively; 47, 06% do physical exercise for about 3 to 5 times a week; 90.2% do not consume cigarette; 82.35% do not consume alcohol; The knowledge about diabetes is good in 64.71%. Keywords: mellitus diabetes, lifestyles.